Genetic Susceptibility to Fungal Infections and Links to Human Ancestry - Naik, Bharati; Ahmed, Sumayyah M. Q.; Laha, Suparna; Das, Shankar Prasad (Frontiers in Genetics, 2021)
Over the ages fungi have associated with different parts of the human body and established commensal association with its host. They are mostly commensal in nature unless there are certain not so well-defined factors that trigger the conversion from commensal state to a pathogenic state. Some of the factors that induce such transition can be dependent on the fungal species, environment, immunological status of the individual and most importantly host genetics. In this review, we discuss the different aspect of how host genetics play a role in fungal infection, since mutations in several genes make hosts susceptible to such infections. We evaluate how mutations modulate the key recognition between the Pathogen Associated Molecular Patterns (PAMP) and the host Pattern Recognition Receptor (PRR) molecules. We discuss the polymorphisms in the genes of the immune system, how it affects some common fungal infections, highlight on how the immunological status of the host determines fungal recognition and cross reactivity of some fungal antigens against human proteins that mimic them. We highlight the importance of SNPs that are associated with several of the receptor coding genes and discuss how it affects the signaling cascade post infection, immune evasion and autoimmune disorders. As part of personalized medicine, we need application of next generation techniques as a feasible option to incorporate individual’s susceptibility profile towards fungal infections based on genetic predisposition. Finally, we discuss the importance of studying genomic ancestry and understand how genetic differences between human race is linked to variation in fungal disease susceptibility.